ANALISIS TINDAK PIDANA PENCUCIAN UANG DALAM PENGUNGKAPAN KASUS NARKOTIKA - Dio Morrel Rae Sembiring Depari; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research was conducted with the aim of providing an overview of the analysis of money laundering crimes in disclosing narcotics cases. The research method used is qualitative research. The results of this study indicate that money laundering and narcotics crimes are closely related and cannot be separated. Because the crime of money laundering always begins with the disclosure of narcotics cases. Therefore synergy between law enforcers is needed, in order to create a good legal structure, legal culture, and legal substance.Keywords: law, narcotics, money laundering.